Women’s Glass Ceiling Beliefs as Mediators in the rela-tion between Workplace Spirituality and Subjective Success (IITM Journal of Business Studies, 2024)
Objective: To determine whether glass ceiling  beliefs mediate the relationship between  workplace spirituality and subjective success  among women managers serving in Banks in  India. Method: Data was collected from 500 women  managers serving in 3 public sector, 3 Indian  private sector and 4 foreign banks in India.  Structural Equation Modelling was run to  determine the relationship among the constructs.  Result: It was found that Workplace Spirituality  significantly predicted Subjective Success.  Additionally, two glass ceiling beliefs viz., denial  and resilience mediated the relationship between  workplace spirituality and subjective success. Conclusion: Organisations must employ  workplace spirituality interventions to im-prove  the subjective success of women.Originality: The findings offer a novel  perspective on improving women’s chances of  career advancement by enhancing workplace  spirituality. This is the first in-depth study to  focus on the mediating effect of glass ceiling  beliefs and study the percep-tion of women  regarding the glass ceiling in Banks in India.
Keywords: Workplace Spirituality; Glass Ceiling Beliefs; Subjective Success; Women Managers; Banks